PENGARUH PANDANGAN IKLAN, KREDIBILITAS IKLAN, DAYA TARIK IKLAN DAN KEKUATAN IKLAN TERHADAP MINAT BELI (Studi Kasus Penggunaan Sepeda Motor Matic Beat di Kota Bengkulu) - Alim, Meiby Yasir; Kusuma, Merta (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
Consumer buying interest is a source of motivation that encourages consumers to do what they want to do when they are free to choose, when consumers judge that something can be useful, they can become interested, then this can bring satisfaction, when satisfaction decreases then their interest can also decrease. So interest is not permanent, but interest is temporary or can change. This type of research is a quantitative approach. The method used in this research is descriptive method. Data collection methods used here include interviews, observation, documentation, and questionnaires. Based on the results of research on the influence of advertising views, advertising credibility, advertising attractiveness and advertising strength on purchasing decisions of Beat automatic motorbike users in Bengkulu City, Bengkulu, the Fsig value is 0.000 < 0.05 and Fcount > Ftable (42.612> 2.47) , so it can be concluded that together the views of the advertisement, the credibility of the advertisement, the attractiveness of the advertisement and the strength of the advertisement influence the purchasing decisions of users of Beat automatic motorbikes in Bengkulu City. Keywords: Views, Credibility, Attractiveness, Advertising Strength, Purchase Interest